Life-cycle assessment of typical Portuguese cork oak woodlands. - González-García, Sara; Dias, Ana Cláudia; Arroja, Luis (The Science of the total environment, 2013)
Cork forest systems are responsible for making an important economic contribution to the Mediterranean region, especially Portugal where the cork oak woodlands or montados contain about 32% of the world's area. The environmental profile derived from reproduction cork production and extraction in two Portuguese regions (Tagus valley and Alentejo) representative of the Portuguese sector were assessed in detail using the Life-Cycle Assessment (LCA) methodology from a cradle-to-gate perspective. The production line was divided into four stages considering all the processes involved: stand establishment, stand management, cork stripping and field recovery. According to the environmental results, there were remarkable differences between the two production scenarios mainly due to the intensity and repetition of forest activities even though the cork yield was reported to be the same. The management system in the Alentejo region presented the worse environmental profile in almost all the impact categories under assessment, mainly due to the shorter cycle duration of the mechanical cleaning and pruning processes. Cork stripping was identified in both scenarios as the production stage with the highest contribution to the environmental profile due to the cleaning and pruning processes. A sensitivity assessment concerning the cork yield was performed since the average production yields in the Portuguese montados are lower than the ones used in this study. Thus, if the cork yield is reduced, the environmental profile in both scenarios gets worse since almost all the forest activities involved are the same.
Keywords: Environment; Environmental impact; Forestry; Forestry: methods; montado; Portugal; Quercus; Quercus suber L.; Reproduction cork; Trees

A step towards the use of biomonitors as estimators of atmospheric PAHs for regulatory purposes. - Augusto, Sofia; Pereira, Maria J.; Máguas, Cristina; Branquinho, Cristina (Chemosphere, 2013)
One of the main drawbacks of using lichens to monitor atmospheric PAHs has been reported as the inexistence of studies aiming to translate PAH values in lichens into the atmospheric equivalents ones, in order to use this information for regulatory purposes. In this work, PAH concentrations in lichens were compared with PAH concentrations measured in a conventional active sampler in an outdoor environment for a 9-month span. Significant positive correlations between HMW-PAHs, Σ16 EPA-PAHs, and BaP equivalent concentrations in lichens and those in air (TSP) were found. Concentrations of Σ16 EPA-PAHs in lichens and air showed a seasonal variation, with highest values during winter and lowest values during summer. Meteorological variables - temperature, atmospheric pressure, relative humidity, and wind speed - showed to significantly influence PAH concentrations in both lichens and air. Based on the significant linear correlations, equations for translating PAH concentrations measured in lichens into equivalent ones for air were proposed for the first time, allowing a broader use of lichens' information regarding PAHs in monitoring schemes and decision-making.
The following values have no corresponding Zotero field: publisher: Elsevier Ltd accession-num: 23668962
Keywords: Air; BaP; Biomonitors; Environment; Human health; PAHs

Changes in land cover and vegetation carbon stocks in Andalusia, Southern Spain (1956-2007). - Muñoz-Rojas, M; De la Rosa, D; Zavala, L M; JORDÁN, A; Anaya-Romero, M (The Science of the total environment, 2011)
Land use has significantly changed during the recent decades at global and local scale, while the importance of ecosystems as sources/sinks of C has been highlighted, emphasizing the global impact of land use changes. Land use changes can increase C loss rates which are extremely difficult to reverse, in the short term, opposite to organic carbon (OC) which accumulates in soil in the long-term. The aim of this research is to improve and test methodologies to assess land cover change (LCC) dynamics and temporal and spatial variability in C stored in vegetation at a wide scale. LCCs between 1956 and 2007 in Andalusia (Southern Spain) were selected for this pilot study, assessed by comparison of spatial data from 1956 to 2007 and were reclassified following land cover flows (LCFs) reported in major areas in Europe. Carbon vegetation densities were related to land cover, and C vegetation stocks for 1956 and 2007 were calculated by multiplying C density for each land cover class with land cover areas. The study area has supported important changes during the studied period with significant consequences for vegetation C stocks, mainly due to afforestation and intensification of agriculture, resulting in a total vegetation C stock of 156.08Tg in 2007, with an increase of 17.24Tg since 1956. This study demonstrates the importance of LCC for C sequestration in vegetation from Mediterranean areas, highlighting possible directions for management policies in order to mitigate climate change as well as promoting land conservation. The methodologies and information generated in this project will be a useful basis for designing land management strategies helpful for decision makers.
Keywords: Agriculture; Agriculture: statistics & numerical data; Carbon; Carbon Sequestration; Carbon: analysis; Carbon: metabolism; Cities; Cities: statistics & numerical data; climate change; Conservation of Natural Resources; CORINE Land Cover; Environment; Environmental Monitoring; Land use planning; Plant Development; Plants; Plants: chemistry; Plants: metabolism; Soil Pollutants; Soil Pollutants: analysis; Soil Pollutants: metabolism; Spain; Sustainable land management

Plant neighbour identity matters to belowground interactions under controlled conditions. - Armas, Cristina; Pugnaire, Francisco Ignacio (PloS one, 2011)
Root competition is an almost ubiquitous feature of plant communities with profound effects on their structure and composition. Far beyond the traditional view that plants interact mainly through resource depletion (exploitation competition), roots are known to be able to interact with their environment using a large variety of mechanisms that may inhibit or enhance access of other roots to the resource or affect plant growth (contest interactions). However, an extensive analysis on how these contest root interactions may affect species interaction abilities is almost lacking.
The following values have no corresponding Zotero field: accession-num: 22114696
Keywords: biomass; citation; Ecosystem; Environment; Plant Development; Plant Roots; Plant Roots: growth & development; Species Specificity

Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G.; Atkinson, R.; Rokas, A.; Csoka, G.; Nieves-Aldrey, J. L.; Csoka, G.; Nieves-Aldrey, J. L. (MOLECULAR ECOLOGY, 2001)
The Marble gallwasp Andricus kollari has a native range divided into two geographically separated lifecycles. In Eastern Europe and Turkey, the lifecycle involves a sexual generation on Turkey oak, Quercus cerris, while in Iberia and North Africa the sexual generation host is cork oak, Q. suber. Over the last 500 years, A. kollari has expanded its range into northern Europe, following human planting of Q. cem's from Italy and the Balkans. We ask: (i) what is the genetic relationship between eastern and western distributions of Andricus kollari? Can we determine which lifecycle is ancestral, and how long ago they diverged? (ii) To what extent have eastern and western native ranges contributed to northwards range expansion? (iii) Is there any evidence for hybridization between the two life cycle types? We present analyses of allozyme data for 13 polymorphic loci and of sequence variation for a 433 bp fragment of the mitochondrial cytochrome b gene. These show: (i) that four haplotype lineages (one in Spain, two in Hungary/Italy and one in Turkey) diverged more or less simultaneously between 1 and 2 million years ago, suggesting the existence of at least four refuges through recent ice age cycles. Our data cannot resolve which lifecycle type is ancestral. (ii) Populations north of putative refuges are divided into two sets. Populations in south-west France are allied to Spain, while ail remaining populations in northern Europe have been colonized from Italy and the Balkans. (iii) The transition from one race to another in south-west France is marked by abrupt transitions in the frequency of refuge-specific private alleles and corresponds closely to the northern limit of the distribution of cork oak. Although hybrids were detected in north-west France, none were detected where the two lifecycles meet in south-western France. The biology of oak gallwasps predicts that any hybrid zone will be narrow and limited to regions where Q. cem's and Q. suber meet. Our data suggest that eastern and western A. kollari are effectively separate species.
From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)The following values have no corresponding Zotero field: pub-location: COMMERCE PLACE, 350 MAIN ST, MALDEN 02148, MA USA publisher: WILEY-BLACKWELL accession-num: 11298986
Keywords: Alleles; Andricus; Animals; Base Sequence; Cellulose Acetate; Cytochrome b Group; Cytochrome b Group: chemistry; Cytochrome b Group: genetics; DNA; Electrophoresis; Environment; EUROPE; Evolution; Female; gallwasp; Genetic Variation; Genetic Variation: physiology; glacial refugia; host race; Hymenoptera; Hymenoptera: genetics; Hymenoptera: growth & development; Hymenoptera: physiology; invasion; Life Cycle Stages; Mitochondrial; Mitochondrial: chemistry; Mitochondrial: isolation & purification; Molecular; Molecular Sequence Data; Parthenogenesis; phylogeny; Polymerase Chain Reaction; range expansion; Sequence Alignment; Sequence Analysis

Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L; Csoka, G; Nieves-Aldrey, J L (MOLECULAR ECOLOGY, 2001)
The Marble gallwasp Andricus kollari has a native range divided into two geographically separated lifecycles. In Eastern Europe and Turkey, the lifecycle involves a sexual generation on Turkey oak, Quercus cerris, while in Iberia and North Africa the sexual generation host is cork oak, Q. suber. Over the last 500 years, A. kollari has expanded its range into northern Europe, following human planting of Q. cem's from Italy and the Balkans. We ask: (i) what is the genetic relationship between eastern and western distributions of Andricus kollari? Can we determine which lifecycle is ancestral, and how long ago they diverged? (ii) To what extent have eastern and western native ranges contributed to northwards range expansion? (iii) Is there any evidence for hybridization between the two life cycle types? We present analyses of allozyme data for 13 polymorphic loci and of sequence variation for a 433 bp fragment of the mitochondrial cytochrome b gene. These show: (i) that four haplotype lineages (one in Spain, two in Hungary/Italy and one in Turkey) diverged more or less simultaneously between 1 and 2 million years ago, suggesting the existence of at least four refuges through recent ice age cycles. Our data cannot resolve which lifecycle type is ancestral. (ii) Populations north of putative refuges are divided into two sets. Populations in south-west France are allied to Spain, while ail remaining populations in northern Europe have been colonized from Italy and the Balkans. (iii) The transition from one race to another in south-west France is marked by abrupt transitions in the frequency of refuge-specific private alleles and corresponds closely to the northern limit of the distribution of cork oak. Although hybrids were detected in north-west France, none were detected where the two lifecycles meet in south-western France. The biology of oak gallwasps predicts that any hybrid zone will be narrow and limited to regions where Q. cem's and Q. suber meet. Our data suggest that eastern and western A. kollari are effectively separate species.
From Duplicate 2 (Differential success in northwards range expansion between ecotypes of the marble gallwasp Andricus kollari: a tale of two lifecycles - Stone, G; Atkinson, R; Rokas, A; Csoka, G; Nieves-Aldrey, J L)
Keywords: Alleles; Andricus; Animals; Base Sequence; Cellulose Acetate; Cytochrome b Group; Cytochrome b Group: chemistry; Cytochrome b Group: genetics; DNA; Electrophoresis; Environment; EUROPE; Evolution; Female; gallwasp; Genetic Variation; Genetic Variation: physiology; glacial refugia; host race; Hymenoptera; Hymenoptera: genetics; Hymenoptera: growth & development; Hymenoptera: physiology; invasion; Life Cycle Stages; Mitochondrial; Mitochondrial: chemistry; Mitochondrial: isolation & purification; Molecular; Molecular Sequence Data; Parthenogenesis; phylogeny; Polymerase Chain Reaction; range expansion; Sequence Alignment; Sequence Analysis

Agriculture and landscape in Portugal - Firmino, Ana (Landscape and Urban Planning, 1999)
Landscape is the result of a dynamic process, which changes either due to natural causes or due to human impact. Therefore, we cannot expect landscapes to stay unchangeable, although some are evolving more quickly than others. Portugal is a mosaic of landscapes, partly because of different climatic conditions and orographic and morphologic genesis but also because of the impact of human activity, especially in agriculture. This article deals with the impacts of this sector on the landscapes, the consequences of which can be found not only in the ecosystems but also in the daily life of the people, in their jobs, in the abandonment of the land and in the change of mentality, related to the inadequate national policies and the overestimation of short-term economic pro®t
Keywords: agri-environmental measures; Environment; Portugal

Agriculture and landscape in Portugal - Firmino, Ana (Landscape and Urban Planning, 1999)
Landscape is the result of a dynamic process, which changes either due to natural causes or due to human impact. Therefore, we cannot expect landscapes to stay unchangeable, although some are evolving more quickly than others. Portugal is a mosaic of landscapes, partly because of different climatic conditions and orographic and morphologic genesis but also because of the impact of human activity, especially in agriculture. This article deals with the impacts of this sector on the landscapes, the consequences of which can be found not only in the ecosystems but also in the daily life of the people, in their jobs, in the abandonment of the land and in the change of mentality, related to the inadequate national policies and the overestimation of short-term economic pro®t
Keywords: agri-environmental measures; Environment; Portugal

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D; Rodríguez, J; Sanz, J M; Merino, J (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Response of two populations of holm oak (Quercus rotundifolia Lam.) to sulfur dioxide. - García, D.; Rodríguez, J.; Sanz, J. M.; Merino, J. (Ecotoxicology and environmental safety, 1998)
Experiments were carried out with seedlings of Quercus rotundifolia Lam., an evergreen schlerophyllous tree typical of the Spanish Mediterranean climate environments. Fruits were collected in two distant (800 km) populations located in the center (southern Spain) and northern border (northern Spain) of the area of distribution of the species. One-month-old potted plants were grown for 130 days in an enriched atmosphere of SO2 (0.23 ppm, 14 h/day) in controlled (growth chamber) conditions. Both northern and southern plants underwent a significant decrease in growth rate as a consequence of the treatment. Even so, plants appear to be quite resistant to SO2 compared with either more temperate or more productive species. The southern population was more sensitive to the treatment, as reflected by the bigger decrease in both growth and photosynthetic rates. Differences in resistance appear to be related to the biogeographic origin of the populations studied, which underlines the importance of biogeographic aspects in studies of resistance to air pollutants.
The following values have no corresponding Zotero field: accession-num: 9626534
Keywords: Adaptation; Air Pollutants; Air Pollutants: adverse effects; air pollution; biomass; Environment; GROWTH RATE; photosynthesis; Photosynthesis: physiology; Physiological; Plant physiology; Pollutants; Quercus rotundifolia; Sulfur Dioxide; Sulfur Dioxide: adverse effects; Sulphur dioxide; Trees; Trees: drug effects; Trees: genetics; Trees: physiology

Vegetational response to holocene climatic change: Pollen and palaeolimnological data from the Middle Atlas, Morocco - Lamb, H F; VanderKaars, S (HOLOCENE, 1995)
Pollen data from a radiocarbon-dated lake-sediment core from the Middle Atlas of Morocco show that forests of evergreen and winter-deciduous oaks (Quercus rotundifolia, Q. canariensis), present from the start of the Holocene, were invaded at 6200 BP by Cedrus atlantica in low numbers. Two thousand years later, after a short period characterized by higher deciduous oak frequency, Cedrus increased to its present abundance. These changes may have been in response to increasing effective moisture as summer temperatures decreased with declining northern-hemisphere seasonality, under the influence of precessional forcing. Palaeolimnological data from the same core show that the lake level fell sharply in five 200-400 yr-long and intervals, but the pollen data show little or no evidence of a vegetational response. This suggests that summer (growing-season) rainfall remained adequate during the dry intervals, whereas depletion of the groundwater aquifer was the result of reduced winter precipitation. Anthropogenic exploitation since c. 1300 BP has had a greater effect on the forest ecosystem than any of the Holocene and intervals.
Keywords: climatic change; Environment; Palaeolimnology; pollen